ANALISIS PROSES PENGAMBILAN KEPUTUSAN GAMER PADA GAME LIFE IS STRANGE - Bramana, Yogi Marta; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2020)
ABSTRACT Individuals will be treated to a variety of choices and decisions that must be taken in life. Like the decisions taken in the Game whose purpose is for entertainment. Game is one of the new digital media that has a function as entertainment, and individuals who play games with high intensity of time are called gamers. One game that has a decision making process simulation is Life is Strange. The results indicate Feeling and belief affect the judgment of gamers to the characters in the game Life is Strange. This assessment is a factor that influences how all four gamers make decisions throughout the game. When gamers' judgment of one character in the game is bad, the decision taken is a decision that will harm the character. Vice versa, if gamers judge the character of the other person is good then the decision taken will be beneficial for the character. Keywords: Decision Making Process, Gamers, Life is Strange, Feelings, Assessment